2017
DOI: 10.1039/c7ra04267a
|View full text |Cite
|
Sign up to set email alerts
|

Highly oxygenated caryophyllene-type and drimane-type sesquiterpenes from Pestalotiopsis adusta, an endophytic fungus of Sinopodophyllum hexandrum

Abstract: Four new highly oxidized caryophyllene-type sesquiterpenes (1–4), and two new drimane-type sesquiterpenes (6, 7), along with nine known compounds have been isolated from an endophytic fungus Pestalotiopsis adusta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…Moreover, three methyl signals with a singlet ( δ H 1.07 s, 1.07 s, and 0.93 s; 32.1 CH 3 , 24.3 CH 3 , and 18.3 CH 3 ) were also observed in the 1 H and 13 C NMR spectra of 1 . The above characteristic NMR data revealed that 1 should be a drimane-type sesquiterpene with a lactone ring [17,18,19]. Comparison of the NMR data of 1 with those of strobilactone B from the marine-derived fungus Aspergillus ustus [20] suggested that 1 shares a similar nucleus structure with the known compound strobilactone B.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, three methyl signals with a singlet ( δ H 1.07 s, 1.07 s, and 0.93 s; 32.1 CH 3 , 24.3 CH 3 , and 18.3 CH 3 ) were also observed in the 1 H and 13 C NMR spectra of 1 . The above characteristic NMR data revealed that 1 should be a drimane-type sesquiterpene with a lactone ring [17,18,19]. Comparison of the NMR data of 1 with those of strobilactone B from the marine-derived fungus Aspergillus ustus [20] suggested that 1 shares a similar nucleus structure with the known compound strobilactone B.…”
Section: Resultsmentioning
confidence: 99%
“…Including a trans -endocyclic (4–5) double bond in the nine-membered ring of caryophyllane system leads to the generation of the caryophyllene skeleton [ 115 ]. This structure is susceptible to rearrangements and cyclization reactions, thus allowing the formation of various polycyclic derivatives, such as pestaloporins, highly oxygenated caryophyllene-type sesquiterpenes, bicyclohumulenone, and bicyclohumuladiol [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ].…”
Section: Caryophyllane Sesquiterpenesmentioning
confidence: 99%
“…Although several novel caryophyllane-type molecules (e.g., rumphellatins, cytosporinols, suberosols, kobusone, isokobusone, rumphellolides, nanonorcaryophyllenes, pestalotiopsins, pestaloporonins, punctatins, and punctaporins) have been identified in different natural kingdoms [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ], because of the limited characterization of their pharmacological properties, the present overview is focused on the most representative compounds isolated from plants, i.e., β-caryophyllene, β-caryophyllene oxide, α-humulene, and isocaryophyllene.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical studies of the resulting crude extracts had afforded two cytotoxic spiroketals and their putative biosynthetic precursors ( Liu et al, 2016a ), nine cytotoxic and antioxidant polyketides ( Guo et al, 2020a ), and five cytotoxic caryophyllene-derived sesquiterpenoids with 4/6/5 ring system ( Guo et al, 2020b ). Further chemical investigations of these fractions led to the isolation of two new humulane-derived sesquiterpeniods, pestalothenins A ( 1 ) and B ( 2 ), one new caryophyllene-derived sesquiterpeniod pestalothenin C ( 3 ), together with five known compounds, 14-acetylhumulane ( 4 ) ( Liu et al, 2016b ), 9,15-Dihydroxy-2,6-humuladiene-5,10-dione ( 5 ) ( Pulici et al, 1996a ), punctaporonin H ( 6 ) ( Wu et al, 2014 ), pestalotiopsin E ( 7 ) ( Xiao et al, 2017 ), and pestalotiopsin C ( 8 ) ( Pulici et al, 1997 ; Figure 1 ). Here we report the isolation, structure elucidation and biological activities of these compounds.…”
Section: Introductionmentioning
confidence: 99%